Otomatisasi Pengolahan Data Pada Sistem Pelayanan Rental CD Tisanda - Yunianto, Mochtar; Wahyu Utami, Yustina Retno (Gaung Informatika, 2011)
CD rental at Tisanda is uncomputerized that caused slow in time and energy-consuming transaction. Information System of CD rental is an alternative solution to solve problem in the data analysis. CD rental information system is a system that has borrowing and repayment process, including providing information about the number of existing CDs. This study discusses lending transactions, refunds, and penalties. This research method is observation, interviews, and literature. The system is built using Visual Basic as the language program and mySQL as database with mysql-connector-odbc-win32-3:51:23 as connectors. CD Rental Information System includes the CD report, rent, damage, and loss of earnings. This system is more efficient because it can minimize data storage. In addition, it takes less energy and need a short time to input data or reports and data can be accessed more quickly than before. Rental Information System at Tisanda also uses a barcode reader so the transactions can be faster.